Molecular Docking and 3D Qsar Studies of C000000956 as a Potent Inhibitor of Bace-1 - Joseph, Ogunleye Adewale; Babatomiwa, Kikiowo; Niyi, Adelakun; Olaposi, Omotuyi; Olumide, Inyang (Drug Research, 2019)
Background BACE-1 is an aspartate protease that is responsible for the proteolysis of amyloid precursor proteins (APP) into beta-amyloid (Aβ), a neurotoxic peptide in patients with Alzheimer’s disease (AD). As such, BACE-1 is a prime pharmacological target in the control of Aβ in the brain and its inhibition will be a sound approach in AD therapy.Methods The computational pipeline which comprised molecular docking (MD), Quantitative Structure Activity Relationship (QSAR) modelling and Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) studies enabled the prediction of molecular interaction and relative inhibitory potentials of the hit compound.Results and Discussion The current study reports a naturally sourced small molecule inhibitor of BACE1 (C000000956) which was obtained through a computational pipeline. Also, pharmacological constraints such as pH dependent activity of the enzyme and blood brain barrier permeation which have been associated with the efficacy of previous BACE-1 inhibitors were well catered for. Our results suggest that orally delivered C000000956 is a potential small molecule inhibitor of BACE-1 which may find usefulness in AD-therapy.
Keywords: Alzheimer’s disease; beta-secretase (BACE1); aspartyl dyad; ADME studies; molecular docking; QSAR modelling